2023
DOI: 10.1186/s12888-023-04823-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factors related to maternal anxiety during pregnancy among women referred to Tabriz primary care centers

Abstract: Background Maternal anxiety during pregnancy is sometimes considered a normal mechanism to overcome the mother’s mental preoccupation with having a child. However, stress and anxiety might become a medical condition, becoming so severe as to affect the mother’s mental health. Therefore, the present study aimed to investigate factors related to maternal anxiety during pregnancy in women referring to prenatal primary care centers in Tabriz. Methods T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…According to a review anxiety often comes and derived from many circumstances between the internal environment and the psychological changes in mothers. 4 …”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…According to a review anxiety often comes and derived from many circumstances between the internal environment and the psychological changes in mothers. 4 …”
Section: Dear Editormentioning
confidence: 99%
“…According to a review anxiety often comes and derived from many circumstances between the internal environment and the psychological changes in mothers. 4 This study's technique indicated an effective effort in evaluating the association between maternal anxiety during mid-pregnancy and new-born sleep conditions. One of the study's main strengths was its meticulous attention to detail in data gathering and quality control processes.…”
mentioning
confidence: 99%